Convergence in capacity and applications
In this article we prove that if u_j, v_j, wE(Ω) such that u_j,v_j≥ w, j≥ 1, and |u_j-v_j|→ 0 in C_n-capacity, then _j→∞h(φ_1,…,φ_m) [(dd^cu_j)^n-(dd^cv_j)^n]=0 in the weak-topology of measures for all φ_1,… ,φ_mPSH L_loc ^∞ (Ω), hC(R^m). We shall then use this result to give some applications., number=1, journal=Mathematica Scandinavica, author=Hiep, Pham Hoang, year=2010, month=Sep., pages=90–102